Terjemah Edip Yuksel, dkk. Atas Q.S. An-Nisa [4]: 2-6 - Su’di, M. Zaid (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2019)
Q.S. an-Nisa ', especially verse 3, including verses which are often polemic. Some opinions set it as legitimacy to allow the practice of polygamy to be loose. With the support of this verse the promotion of polygamy is carried out openly. Seminars or training to teach polygamy are also openly held in the media. This paper attempts to outline Edip Yuksel's views in understanding the context of the Qur'anic interpretations relating to the practice of polygamy. The translation project conducted by Edip Yuksel et al. has given rise to a lot of controversy (besides Yuksel's own controversial personality). His method of trying to escape the influence of old interpretations offers a fresh perspective that is different from traditional interpretations from both Sunnis, Shiites and academics. But it does need a lot of study to prove whether Yuksel really can bring accurate readings, as he said, to the Qur'an. His reading of yamin milk, for example, which most scholars interpreted as slaves by Yuksel was translated as a woman's wife who chose to establish contracts with Muslims. Although semantically it has a foundation, but it needs historical tracing whether there are such cases or is it merely a projection from Yuksel. Because the Koran is somehow born in a certain context, and often is a response to real cases that appear in his time.